2022
DOI: 10.1371/journal.pone.0272949
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes following in vitro fertilization treatment in women with previous recurrent ectopic pregnancy

Abstract: Objectives The aim of this study was to investigate the impact of a history of recurrent ectopic pregnancy (EP) on pregnancy outcomes of subsequent in vitro fertilization (IVF) treatment. Methods A retrospective cohort study involving 457 women with a history of recurrent EP (REP group), 912 women with a history of single EP (SEP group), and 1169 women with a history of intrauterine pregnancy (IUP group) as the control group, was conducted. IVF outcomes were compared for each cohort. Results The incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…With the improvement of IVF technique and IVF treatment affordability, the role of ART in EP population becomes increasingly significant.. The study conducted by Yamei Xue et al found there was no difference in pregnancy rate, live birth rate, miscarriage rate and ectopic rate in IVF patients regarding of EP history [18]. Same result was found, He Cai et al revealed no statistically difference in live birth rate and recurrent EP rate comparing patient with EP, intrauterine pregnancy or never had conceived [19].…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of IVF technique and IVF treatment affordability, the role of ART in EP population becomes increasingly significant.. The study conducted by Yamei Xue et al found there was no difference in pregnancy rate, live birth rate, miscarriage rate and ectopic rate in IVF patients regarding of EP history [18]. Same result was found, He Cai et al revealed no statistically difference in live birth rate and recurrent EP rate comparing patient with EP, intrauterine pregnancy or never had conceived [19].…”
Section: Discussionmentioning
confidence: 99%